2008
DOI: 10.1016/j.oraloncology.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET in oral and oropharyngeal cancer. Value for confirmation of N0 neck and detection of occult metastases

Abstract: FDG PET in oral and oropharyngeal cancer. Value for confirmation of N0 neck and detection of occult metastases Krabbe, Christiaan A.; Dijkstra, Pieter U. ; Pruim, Jan; van der Laan, Bernard F.A.M.; van der Wal, Jacqueline E.; Gravendeel, Joost P.; Roodenburg, Johannes Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 27 publications
2
27
0
1
Order By: Relevance
“…The subjects in our study strongly agreed that PET scan can determine the extent of their location and number of metastasis. This is in accordance with the results obtained by Krabbe et al 19 The respondents strongly agreed with the concept of advising PET scan in pregnant women as the fetal radiation dose from 18 F-FDG PET is quite low and significantly below the threshold dose for deterministic effects. Although F-FDG is believed to cross the placental membrane and accumulate in the fetus, there are no scientific studies documenting the fetal toxicity associated with it.…”
Section: Discussionsupporting
confidence: 90%
“…The subjects in our study strongly agreed that PET scan can determine the extent of their location and number of metastasis. This is in accordance with the results obtained by Krabbe et al 19 The respondents strongly agreed with the concept of advising PET scan in pregnant women as the fetal radiation dose from 18 F-FDG PET is quite low and significantly below the threshold dose for deterministic effects. Although F-FDG is believed to cross the placental membrane and accumulate in the fetus, there are no scientific studies documenting the fetal toxicity associated with it.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have compared diagnostic accuracy in the evaluation of cervical nodal metastasis in head and neck SCC between different imaging modalities including CT, MRI, US, and F-18 FDG PET (17,18,20,21,23,25,27,(30)(31)(32)(33)(34)(50)(51)(52). Adams et al compared F-18 FDG PET with conventional imaging modalities (CT, MRI, and US) in the lymph node staging of 60 patients with head and neck SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Stand alone 18 F-FDG PET is either complementary to, or shows a better performance in detecting cervical metastases than, CT or MRI 2,21,22 . The accuracy of 18 F-FDG PET in detecting cervical metastases, is not optimal as small cervical metastases can be missed, especially concerning the clinically N0 neck 6,13,16,32 . Although several studies showed that PET/CT is more accurate in staging than CT, PET or MRI alone 8,9,16,31 , data available on the value of PET/CT in detecting cervical metastases are scarce ( Table 7).…”
Section: Discussionmentioning
confidence: 99%